A nationwide study on Sydenham's chorea: Clinical features, treatment and prognostic factors. (January 2022) - Orsini, Alessandro; Foiadelli, Thomas; Magistrali, Mariasole; Carli, Niccolò; Bagnasco, Irene; Dassi, Patrizia; Verrotti, Alberto; Marcotulli, Daniele; Canavese, Carlotta; Nicita, Francesco; Capuano, Alessandro; Marra, Chiara; et al.
Abstract: Objectives: Sydenham's Chorea (SC) is a neuropsychiatric disorder and a major manifestation of acute rheumatic fever. The erroneous assumption that SC is a benign and self-limiting disease, has led to a lack of high-quality scientific evidence of the therapeutical and prognostic features of SC. Study design: We retrospectively analyzed the medical records of patients <18-years old with SC in 17 Italian pediatric centers. Recorded data included clinical, instrumental and laboratory parameters. Prognostic risk factors including treatment regimens were assessed with univariate and multivariate sub-analysis. Results: We included 171 patients with SC. 66% had generalized chorea, and 34% hemichorea. 81% had carditis (subclinical in 65%). Additional neurological symptoms were reported in 60% of the patients, mainly dysarthria and dysgraphia. 51% had neuropsychiatric symptoms at onset, which persisted after 12 months in 10%. Among psychiatric manifestations, the most common was anxiety disorder/depression (77%). Neurological remission was reached by 93% of the patients at 6 months; 9% relapsed. Patients were treated as follows: 11% penicillin alone, 37% immunomodulatory therapy, 16% symptomatic drugs (i.e. anti-seizure medication, dopamine antagonists) and 37% both symptomatic and immunomodulatory treatment. Neurological outcome did not differ between groups. Patients receiving symptomatic drugs had a higher risk of relapse on multivariate analysis (p = 0.045). Conclusions: Treatment of SC was largely heterogeneous. Based on our results, immunomodulatory therapy did not show higher efficacy at medium term, although it was associated to a slightly lower risk of relapse compared to symptomatic therapy. Longitudinal studies are needed to assess specific risk factors and best treatment options. Highlights: SC is a post-streptococcal disease causing a typical movement and psychiatric disorder. Evidence-based guidelines for SC are currently lacking. Treatment heterogeneity was high in our national retrospective multicenter cohort. Treatment with immunotherapy or symptomatic drugs did not differ in terms of outcome. Use of symptomatic drugs was associated with a slight increased risk of relapse.